1993
DOI: 10.1016/0378-1097(93)90392-f
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Escherichia coli strains producing microcins of B and C types

Abstract: A screening of 11956 enterobacteria isolates resulted in selection of seven active microcin-producing strains. The microcins were shown to be peptides or their derivatives with a rather broad spectrum of activity, mainly against Gram-negative bacteria. According to cross-immunity criteria, the microcins studied belonged to two of the previously suggested types, B (five strains) and C (two strains). Those of type B could be further classified into two subtypes on the account of differences in the spectrum of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…MccC7/C51 is active against several genera and species of enterobacteria such as Escherichia , Klebsiella , Salmonella , Shigella, Yersinia and Proteus [66][67][68] . It inhibits the growth of E. coli strains at 100-500 n M .…”
Section: From Structural Diversity To Diverse and Complex Mechanisms mentioning
confidence: 99%
“…MccC7/C51 is active against several genera and species of enterobacteria such as Escherichia , Klebsiella , Salmonella , Shigella, Yersinia and Proteus [66][67][68] . It inhibits the growth of E. coli strains at 100-500 n M .…”
Section: From Structural Diversity To Diverse and Complex Mechanisms mentioning
confidence: 99%
“…Microcin C51 (MccC51) belongs to the modified microcin class. It is a nucleotide-peptide antibiotic (1,178 Da) produced by a natural strain of Escherichia coli isolated in Moscow (Russia) from the feces of a healthy child (14). A recent reinvestigation of the MccC51 structure (3) showed that it differs from the previously published structure (18).…”
mentioning
confidence: 99%
“…MccC51 exhibits a strong antibacterial activity, since it inhibits the growth of different E. coli strains when present at 0.1 to 0.5 g/ml. The spectrum of MccC51 activity includes various genera and species of Enterobacteriaceae such as Enterobacter, Citrobacter, Klebsiella, Salmonella, Shigella, and Yersinia (14,17). MccC51 inhibits protein synthesis (I.…”
mentioning
confidence: 99%
“…Experiments carried out using proteolytic enzymes confirmed the proteinaceous nature of BLIS-400. Trypsin and a-chymotrypsin did not hydrolyse polypeptides in BLIS-400 preparation, probably due to the presence of enzyme inhibitors (Khmel et al 1993). On the contrary, gel electrophoresis indicated that proteinase K was able to degrade BLIS-400, although a residual antimicrobial activity remained after treatment, as reported by others (Risøen et al 2004;Kang and Lee 2005), suggesting partial digestion of the active compound, or production of free active peptide(s) able to kill the sensitive strain.…”
Section: Discussionmentioning
confidence: 97%